American Interconnected Text Theory: A Critical View of Western Reception - Mohamed, Brahim Amri (Journal of Arabic Language Sciences and Literature, 2025)
The encounter between literature and digital technology at the beginning of the third millennium raised a number of issues and raised new questions with a different vision and perspective. But credit goes to the American school, which was the first to present the first theoretical conception of hypertext by Jay D. Boiter, George Landow, Michael Joyce, Stuart Moulthrop, and J. Y. Douglas. This perception can be summarized in what has come to be called the “Theorie de la convergence” theory. In this study, we will attempt to present with a critical view the various opinions of its early critics who accompanied its spread from Europe, Canada, and America, and criticized some of its sayings, trying to address the debate its perceptions and positions raised in the critical arena. We made sure to track a descriptive, comparative approach in the first stage, and a comparative analytical approach in the second stage. The article is not a criticism of the opinions of Western scholars of convergence theory, but rather a criticism of its various criticisms. Therefore, it seemed to us that this dual approach, which initially reviews the opinions objectively, and then analyzes these critical opinions secondly from a critical perspective, is the most appropriate in such cases. The purpose of this is to present the first theory of interconnected text to the Arab reader from its original sources, but from a perspective that is not devoid of a critical sense that gives consideration to its authors first, and does justice to its critics second.
Keywords: convergence theory; connected text; interactivity; ending; link; Landow